Efeito do treinamento de força com restrição do fluxo sanguíneo sobre a atividade metaborreflexa em jovens saudáveis - Farias, Rafael Riera de (2017)
Ischemic training (IT) has been proposed as a tool to induce muscle hypertrophy, but its safety remains controversial as it may cause mean blood pressure (MBP) increments due to the activation of the muscle metaboreflex (MM). However, IT also causes metabolites accumulation that in turn may desensitise type III and IV nerve endings, which are thought to trigger the MM1. Then, we hypothesised that a period of IT would result in a blunted hemodynamic activation during the MM. In order to evaluate the effect of IT on heart rate (HR), ventricular filling time, systolic volume ratio / left ventricular ejection time, MAP, systolic volume (SV), cardiac output (CO), and peripheral vascular resistance (PVR) to the activation of MM in healthy youngsters. 17 young healthy male (age 21±2 yrs) took part in this study. Hemodynamics during the MM was obtained by the method of the post-exercise muscle ischemia2 at baseline (T0) and after one month (T1) of dynamic IT (handgrip), conducted at 30% of maximum voluntary contraction in the dominant arm with circulatory occlusion, which was obtained with a pressure of 50 mmHg above systolic blood pressure. IT was applied for 3 days/week. Hemodynamic measurements were assessed by means of impedance cardiograph, which has been commonly employed in resting and exercising subjects. The main results were that none of the studied parameters changed in response to MM after IT. In detail, MBP response was +4.09±3.87 vs. +2.23±4.65 mmHg at T0 and T1 respectively (p>0.05). Similarly, there was no difference in HR (-3.47±9.26 vs 0.81±9.96 bpm), SV (+11.3±20.2 vs. +2.28±13.07 mL), CO (+349±1643.4 vs. +57.2±801.9 mL*l-1), SVR (-14.6±201.6 vs. +5.59±104.9 dynes·s-1·cm-5) and VFR ( 5,8 +/- 2,8 vs 9,3+/- 3,3 ml/s). Contrary to initial hypothesis, this investigation provides evidence that a period of 4 weeks of IT is not able to change the hemodynamic response to metaboreflex activation in young healthy male subjects. Thus, the IT protocol employed in the present investigation was not able to desensitise type III and IV nerve endings.